Measuring European economic integration 1880 - 1913: A new approach - Yaman Kouli; Jörg König (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2021)
Historiography on European integration before 1914 has acknowledged that the level of entanglements between the European nation-states was quite advanced. Indeed, historians were able to confirm a high level of cooperation on the legal, social, technical and even political level. And yet, the exact level of economic integration has hitherto been unknown. In this paper, we quantitatively analyse the level of economic integration in Europe. We develop a comprehensive economic integration index for the period 1880-1913. By exploiting existing as well as newly available databases, we quantitatively analyse the longterm development of European economic integration for 15 European countries. Subindices are developed to measure for each country and each year the extent of European market integration, economic homogeneity and cyclical symmetry. We exploit the data using principal-component-analysis (PCA). Moreover, we test for country-specific characteristics via regression analysis and cluster analysis. With our findings, we are able to show that European economic integration actually declined during the years between 1880 and 1913 and got more fragmentated. Even though the exact picture depends on the country, the tendency is still undeniable: during the "first wave of globalisation", European economic integration levels moved downwards.
Keywords: C38; N93; F15; 330; Economic History; European Economic Integration